Cadmium specific proteomic responses of a highly resistant Pseudomonas aeruginosa san ai. Issue 19 (16th March 2018) - Izrael-Živković, Lidija; Rikalović, Milena; Gojgić-Cvijović, Gordana; Kazazić, Saša; Vrvić, Miroslav; Brčeski, Ilija; Beškoski, Vladimir; Lončarević, Branka; Gopčević, Kristina; Karadžić, Ivanka
Abstract : When exposed to cadmium a highly resistant strain P. aeruginosa san ai responds by an increased metalloprotein expression (particularly denitrification proteins), an enhanced respiration, and a pronounced thiol-disulfide protein modifications. Abstract : Pseudomonas aeruginosa san ai is a promising candidate for bioremediation of cadmium pollution, as it resists a high concentration of up to 7.2 mM of cadmium. Leaving biomass of P. aeruginosa san ai exposed to cadmium has a large biosorption potential, implying its capacity to extract heavy metal from contaminated medium. In the present study, we investigated tolerance and accumulation of cadmium on protein level by shotgun proteomics approach based on liquid chromatography and tandem mass spectrometry coupled with bioinformatics to identify proteins. Size exclusion chromatography was used for protein prefractionation to preserve native forms of metalloproteins and protein complexes. Using this approach a total of 60 proteins were observed as up-regulated in cadmium-amended culture. Almost a third of the total numbers of up-regulated were metalloproteins. Particularly interesting are denitrification proteins which are over expressed but not active, suggesting their protective role in conditions of heavy metal exposure. P. aeruginosa san ai developed a complex mechanism to adapt to cadmium, based on: extracellular biosorption, bioaccumulation, the formation of biofilm, controlled siderophore production, enhanced respiration and modified protein profile. An increased abundance of proteins involved in: cell energy metabolism, including denitrification proteins; amino acid metabolism; cell motility and posttranslational modifications, primarily based on thiol-disulfide exchange, were observed. Enhanced oxygen consumption of biomass in cadmium-amended culture versus control was found. Our results signify that P. aeruginosa san ai is naturally well equipped to overcome and survive high doses of cadmium and, as such, has a great potential for application in bioremediation of cadmium polluted sites.